A MODEL FOR DEVELOPING PARTICIPATORY SCHOOL ADMINISTRATION TO DEVELOP THE QUALITY OF EDUCATION AT BANGPHANENG SCHOOL - Maijandee, Kanittha (Journal of MCU Nakhondhat, 2025)
This research aimed to: 1) Examine the existing problems in the administration of internal supervision; 2) Develop a model for enhancing internal supervision administration; 3) Assess the appropriateness and feasibility of the developed model; 4) Implement the developed model in practice; and 5) Study the satisfaction with using the developed model. The study population was divided into two groups. For quantitative research, the first group comprised 85 participants, including seven teachers, 71 parents, and seven basic education school board members. For qualitative research, the second group consisted of 7 school administrators and seven educational experts. Data collection instruments included questionnaires and in-depth interviews, with item-objective congruence (IOC) values ranging from 0.80 to 1.00. Data analysis involved content analysis and statistical methods, including mean and standard deviation. The research findings were as follows: 1) Analyzing problems in proactive internal supervision administration revealed high overall issues ( = 4.36, = 0.31); 2) The developed model comprised five components: introduction, quality management, internal supervision and administration, success factors, and model implementation; 3) The evaluation of the model’s appropriateness and feasibility indicated that all five components were appropriate and feasible, with IOC values ranging from 0.80 to 1.00, 4) School administrators’ opinions regarding the trial implementation of the model indicated a high level of agreement ( = 4.43, = 0.29). and 5) Overall satisfaction with using the model was high, with an average score of ( = 4.39, = 0.36).